The Revenue Administration-Gap Analysis Program : An Analytical Framework for Excise Duty Gap Estimation - Thackray, Mick (Technical Notes and Manuals; Technical Notes and Manuals ;, 2017)
The IMF Fiscal Affairs Department's Revenue Administration Gap Analysis Program (RA-GAP) assists revenue administrations from IMF member countries in monitoring taxpayer compliance through tax gap analysis. The RA-GAP analytical framework for estimating excise gaps presented in this Technical Note sets out the steps and data required for comprehensive top-down gap estimates based on a comparison of actual collections to potential collections, which is estimated from consumption (or use) and expenditure of excise commodities. The note outlines the motivation for, and different approaches to, excise gap estimation; and identifies the design criteria for robust gap estimates. The note was jointly produced by RA-GAP team and the Slovak Republic's Institute for Financial Policy, piloting the framework for the mineral oils excise gap in Slovakia.